CONTENT ANALYSİS OF ARTİCLE SERİES ON HEALTH (Third Sector Social Economic Review, 2021)
The aim of this study is to analyze the content of health articles contained in the printed version of the Posta Newspaper, one of the major national newspapers ranked fourth in circulation. This qualitative content analysis study is planned retrospectively, cross-sectional, and descriptive. 181 articles were examined within the scope of the study. Most of the time, professionals who titled as Professor Doctors provide information in the articles as a source (56.3% (n=107). In the study, it is determined that the most articles were on neurology (11.1%; n = 21), nutrition and dietetics (10.0%; n = 19) and dermatological and venereal diseases (8.3%; 16). Treatment, disease information, nutrition, health promotion, personal factors, diagnosis, environmental factors, guiding, and preferences were the categories that were revealed in the study. Nutritional advice (254), treatment methods (179), causes of disease (127) and symptoms of disease (110) were coded the most. Media is one of the crucial sources of information. High-popular topics are taken place in health articles. Even if they are not popular, public health issues should also be included. The media should not encourage for unnecessary consumption of health services.
Keywords: Health article series; content analysis; health news; daily article; health publishing